Human Decidual Mesenchymal Stem Cells Obtained From Early Pregnancy Improve Cardiac Revascularization Postinfarction by Activating Ornithine Metabolism - Chen, Kegong; Bai, Long; Lu, Jingtong; Chen, Wei; Liu, Chang; Guo, Erliang; Qin, Xionghai; Jiao, Xuan; Huang, Mingli; Tian, Hai (Frontiers in Cardiovascular Medicine, 2022)
Background: Compared with bone marrow mesenchymal stem cells (BMSCs), decidual mesenchymal stem cells (DMSCs) are easy to obtain and exhibit excellent angiogenic effects, but their role in cell transplantation after myocardial infarction (MI) remains unclear. Methods: BMSCs and DMSCs were harvested from healthy donors. The effects of both cell types on angiogenesis were observed in vitro. Metabonomics analysis was performed to compare different metabolites and screen critical metabolic pathways. The therapeutic effect of DMSCs on MI in rats was assessed based on neovascularization and cardiac remodeling. Results: DMSCs exhibited a better angiogenic effect on human umbilical vein endothelial cells (HUVECs) than BMSCs in vitro. In addition, ornithine metabolism, which is associated with vascularization, was significantly increased in DMSCs. The transplantation of DMSCs in the rat MI model significantly enhanced angiogenesis of the infarct border area and improved cardiac remodeling and dysfunction postinfarction compared with BMSCs. Furthermore, inhibition of ornithine metabolism by silencing ornithine decarboxylase (ODC) in DMSCs partly abolished the benefits of DMSC transplantation. Conclusion: Compared with BMSCs, DMSCs exhibited better efficacy in improving revascularization and heart remodeling post-MI via the activation of ODC-associated ornithine metabolism.